PEMANFAATAN SISTEM PAKAR PADA MASALAH IBU MENYUSUI MENGGUNAKAN METODE FORWARD CHAININGPADA KLINIK BIDAN Z - Effendi, Rustam; Efendi, Yasin; Winasis, Persis Haryo; Putri, Annisa Hartayanti (Journal of Innovation And Future Technology (IFTECH), 2024)
Failure in the breastfeeding process is often caused by several problems, both in the mother and the baby. Often mothers do not know what the problem is and how to solve it. By using the forward chaining method this expert system was built to help provide an initial diagnosis of the problem of breastfeeding mothers. From this expert system can be obtained information about the problem, its definition, symptoms, and initial solution before going to the nearest health worker. Based on the results of using the forward chaining method, this expert system is able to conclude the problem faced based on the symptoms experienced by breastfeeding mothers and provide information on the initial treatment that can be done. Keywords: expert system, forward chaming, breast milk, breastfeeding, diagnosis